A new species of the genus Toleria Walker, [1865] from northern Vietnam and Laos with establishment of a new generic synonymy in Cissuvorini (Lepidoptera, Sesiidae) - Kallies, Axel; Ogane, Hiromichi; Yata, Naoki (Zootaxa, 2020)
A new species of Toleria Walker, [1865], T. aritai Ogane & Kallies spec. nov., is described from Vietnam and Laos. Superficially, it resembles species of the genus Dasysphecia Hampson, 1919 but differs by venation and genitalia characters. The tribe Cissuvorini is briefly reviewed. Chimaerosphecia Strand, [1916] syn. rev. is considered a younger subjective synonym of Toleria. The following new combinations are introduced: Toleria aegerides (Strand, [1916]) comb. nov., Toleria colochelyna (Bryk, 1947) comb. nov., Toleria sinensis (Walker, [1865]) comb. rev. and Glossosphecia sinensis (Wang & Yang, 2002) comb. nov.